Beyond graphene foam, a new form of three-dimensional graphene for supercapacitor electrodes. Issue 5 (14th January 2016) - Zhang, Lu; DeArmond, Derek; Alvarez, Noe T.; Zhao, Daoli; Wang, Tingting; Hou, Guangfeng; Malik, Rachit; Heineman, William R.; Shanov, Vesselin
Abstract : Graphene foam (GF) is a three-dimensional (3D) graphene structure that has been intensively studied as an electrode material for energy storage applications. Here we report a new design and fabrication process of an electrode material called graphene pellet (GP) for energy storage applications. Abstract : Graphene foam (GF) is a three-dimensional (3D) graphene structure that has been intensively studied as an electrode material for energy storage applications. The porous structure and seamlessly connected graphene flakes make GF a promising electrode material for supercapacitors and batteries. However, the electrical conductivity of GF is still unsatisfactory due to the lack of macropore size (∼300 μm) control that hinders its applications. Previously we reported a new seamless 3D graphene structure – graphene pellets (GPs) – with well-controlled mesopore size (∼2 nm), high electrical conductivity (148 S cm −1 ) and good electromechanical properties that differ substantially from the known GF. Here we demonstrate that the obtained 3D graphene structure is an ideal scaffold electrode for pseudocapacitive materials and redox additive electrolyte systems. For example, after electrochemical coating with MnO2, the GP/MnO2 electrode showed specific and volumetric capacitance up to 395 F g −1 and 230 F cm −3 at 1 A g −1, respectively. When combined with a hydroquinone and benzoquinone redox additive electrolyte, the GPs showed a specific capacitance of 7813 F g −1 at 10 A g −1 . Moreover, when the GP/MnO2 electrode was assembled with a GP/polypyrrole electrode, the obtained full cell showed good electrochemical performance with a maximum energy density of 26.7 W h kg −1 and a maximum power density of 32.7 kW kg −1, and a reasonable cycle life for practical application. The ease in material processing combined with the excellent electrical and electromechanical properties makes GPs promising for a variety of energy storage applications.